Workplace Spirituality as Intangible Resource and Capabilities: As Seen in the Evidence of a Telco Company in the Disruptive Era - Indrajaya, Amelia Naim; Kazeroony, Hamid H (UPT Publikasi Ilmiah UNISBA, 2024)
Previous research had analyzed the positive impact of spirit at work and spiritual leadership separately as independent variables toward organizational commitment and job satisfaction but had not examined it all at once through the strategic management resource-based view framework. This quantitative study, using SEM PLS, examined the spiritual leadership intangible resources (Vision, Hope-Faith, Altruistic Love, Meaning Calling, and Membership) as the factors to develop spirit at work capabilities, which positively influence Job Satisfaction and Organizational Commitment as the performance proxies. Based on a survey of the data taken from the biggest Telco company in Indonesia, going through volatile, uncertain, complex, and ambiguous (VUCA) phase, this research shows that spirituality matters in the resource-based view of strategic management framework, where resources and capabilities are intertwined in supporting performance. All hypotheses were significant, implying the criticality of embedding spiritual values in creating a greater purpose for all employees. Further qualitative research in this area would enrich workplace spirituality research.